BIMTEK FTI: Digital Village Governance - Muhammad Nur Hidayat, Andi; Ramadhan, As'ary; Na’im Al Jum’ah, Muhammad (MEKONGGA: Jurnal Pengabdian Masyarakat, 2024)
Currently, with the allocation of village funds from the government, village development has become an interesting topic of discussion. Both from an economic perspective and better village governance. As with most villages in general, the majority of village funds are used for physical development, such as building construction, repairing the village hall, and village infrastructure such as repairing roads and bridges. Considering the importance of digital village governance, the Faculty of Information Technology, Sembilanbelas November Kolaka University will hold FTI 2022 Technical Guidance: Digital Village Governance. The expected impact after this activity is the creation of good village governance based on information/electronic technology. Based on the results of the activities that have been carried out, it can be concluded that the community service program (PKM) activities, collaboration between Sembilanbelas November Kolaka University and village heads within Kolaka Regency have gone well and are able to provide understanding to village officials regarding good village governance. information/electronic technology based.